Salinity Acclimation Strategies in Nitrifying Bioreactors - Navada, Sharada; Vadstein, Olav (Frontiers in Marine Science, 2022)
Several industries, including aquaculture, produce effluents with high or varying salt concentrations. The treatment of such effluents by the biological nitrification process can be challenging, as the microbes performing this process are sensitive to salinity. In certain cases, such as in recirculating aquaculture systems (RAS), it is essential to maintain high nitrification efficiency during salinity changes to prevent ammonia and nitrite toxicity. Therefore, suitable strategies are required to make nitrifying bioreactors tolerant to salinity variations. Although salinity changes can impact the nitrification performance, it has been shown that nitrifying bioreactors can acclimate to salinity variations over several days. This acclimation can be due to the physiological adaptation of the existing microorganisms or due to selection for microorganisms adapted to that salinity regime. Other factors, such as the biofilm matrix, can also play a role in salinity acclimation. Recent studies have shown that microbial management strategies can be applied to improve the salinity tolerance and reduce the recovery time of nitrifying bioreactors. Here, we discuss the existing knowledge on salinity acclimation in nitrifying systems, and recent advances in strategies to make nitrifying biofilms more tolerant to salinity variations. We also propose directions for future research to improve our understanding of the salinity acclimation mechanisms in nitrifying systems.